Review on Skin Disease Seborrheic Dermatitis Along With Its Treatment and Formulary - Bhujbal, Rutuja; Musale, Shreya; Barge, Mrudula; Naikawadi, Nishigandha (Asian Journal of Pharmaceutical Research and Development, 2025)
Seborrheic Dermatitis is common inflammation of the skin, occurring most often on the face, scalp and chest. It is closely related to infantile seborrheic dermatitis, or diaper rash.Seborrheic Dermatitis is particularly common in patient with Parkinson’s disease or with HIV/ AIDS. Yeast of the genus Malassezia has long been regarded as a main predisposing factor, even though causal relationship has not been firmly established. Additional predisposing factors have been described, including sebaceous activity, host immunity (especially HIV infection), epidermal barrier integrity, skin microbiota, endocrine and neurologic factors, and environmental influence. After synthesizing key evidence from the literature, we propose that intrinsic host factors, such as changes in the amount or composition of sebum and/or defective epidermal barrier, rather than Malassezia, may form the basis of SD pathobiology. The resent resurgence of interest in Malassezia yeasts has revived the old hypothesis that seborrheic dermatitis is caused by an altered relationship between these skin commensals and the host. Moreover, the success of antifungal medications in treating seborrheic dermatitis provides new evidence for this view.